The determinants of housing price change of value year-over-year / Saiful Amri A Shafiuddin - A Shafiuddin, Saiful Amri (2019)
This study is focusing on what determinant the Housing Price Change of Value Year-over- Year. The passion of doing this research is due to the reason that housing issue that had been discuss by the government until they revised the policy at Budget 2019. Such dependent variable that had been chosen are the Gross Domestic Product (GDP) Growth, Lending Interest Rate and Official Exchange Rate. The method that been using in this study is Ordinary Least Square (OLS). This study taking the observation on 31 years of data from 1985 until 2015 of Malaysia’s data. This study will be a good reference for other researcher who want to proceed the research on housing price in Malaysia.